Lung Adenocarcinoma Cells Promote Self-Migration and Self-Invasion by Activating Neutrophils to Upregulate Notch3 Expression of Cancer Cells - Peng, Weidong; Sheng, Youjing; Xiao, Han; Ye, Yuanzi; Kwantwi, Louis Boafo; Cheng, Lanqing; Wang, Yuanchong; Xu, Jiegou; Wu, Qiang (Frontiers in Molecular Biosciences, 2022)
Background: Invasion and migration of cancer cells play a key role in lung cancer progression and metastasis. Tumor-associated neutrophils (TANs) are related to poor prognosis in many types of cancer. However, the role of TANs in lung cancer is controversial. In this study, we investigated the effect of TANs on the invasion and migration of lung adenocarcinoma. Methods:Immunohistochemistry was performed to detect the density of infiltrating TANs and the expression of Notch3 in 100 lung adenocarcinoma tissues. Flow cytometry was used to observe the viability of neutrophils, which were isolated from healthy peripheral blood and then exposed to the supernatant of cultured lung adenocarcinoma cell lines. After treating with TANCS (tumor-associated neutrophils culture supernatant), NeuCS (supernatant of cultured neutrophils ), TCCS (supernatant of cultured tumor cells ), Medium (serum-free medium), respectively, the migration and invasion of the lung cancer cells before and after transfected by si-Notch3 were detected by transwell assay and wound healing assay. Kaplan-Meier plotter (http://kmplot.com/analysis/index.php?p,) was used to analyze the prognostic role of the density of TANs on lung adenocarcinoma and TIMER ((http://cistrome.dfci.harvard.edu/TIMER/) was used to detect the expression of Notch3 on lung adenocarcinoma Results: The infiltration of TANs was observed in the parenchyma and stroma of the lung adenocarcinoma, the density of TANs was positively related to the TNM stage and negatively related to the differentiation and prognosis. Notch3 expression of cancer cells was negatively related to the tumor differentiation and prognosis. Compared to quiescent neutrophils, the viability of TCCS-activated neutrophils was enhanced. Both migration and invasion of A549 and PC9 cells were significantly promoted by TANs, while after knocking down Notch3, the migration and invasion of the cancer cells were not affected by TANs. Bioinformatics analysis showed that the density of TANs and the expression of Notch3 were related to the poor prognosis. Conclusion The results indicated that lung adenocarcinoma cells promote self-invasion and self-migration by activating neutrophils to upregulate the Notch3 expression of cancer cells. The density of infiltrating TANs may be a novel marker for the poor prognosis of lung adenocarcinoma. Targeting TANs might be a potential therapeutic strategy for lung cancer treatment.